2014
DOI: 10.1002/pmic.201400092
|View full text |Cite
|
Sign up to set email alerts
|

Probing phosphorylation‐dependent protein interactions within functional domains of histone deacetylase 5 (HDAC5)

Abstract: Class IIa histone deacetylases (HDACs) are critical transcriptional regulators, shuttling between nuclear and cytoplasmic cellular compartments. Within the nucleus, these HDACs repress transcription as components of multi-protein complexes, such as the nuclear co-repressor (NCoR) and beclin-6 co-repressor (BCoR) complexes. Cytoplasmic relocalization releases this transcriptional repressive function. Class IIa HDAC shuttling is controlled, in part, by phosphorylations flanking the nuclear localization signal (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Loss of phosphorylation within an acidic region, the DAC domain, and the NES was shown to modulate HDAC5 protein interactions, including associations necessary for transcriptional repression (12). Interestingly, mass spectrometry-based quantification of HDAC5 phosphorylations within these functional domains showed substantial variation in their relative abundances (12).…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%
See 4 more Smart Citations
“…Loss of phosphorylation within an acidic region, the DAC domain, and the NES was shown to modulate HDAC5 protein interactions, including associations necessary for transcriptional repression (12). Interestingly, mass spectrometry-based quantification of HDAC5 phosphorylations within these functional domains showed substantial variation in their relative abundances (12).…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%
“…Previous HDAC5 structure prediction indicated that the majority of phosphorylations map to the external surface of the protein, suggesting that these modifications may be primarily important for mediating protein interactions (12). Loss of phosphorylation within an acidic region, the DAC domain, and the NES was shown to modulate HDAC5 protein interactions, including associations necessary for transcriptional repression (12).…”
Section: Hdac5-although Numerous Hdac5mentioning
confidence: 99%
See 3 more Smart Citations